Pengaruh Umur Pemanenan Madu di Areal Tanaman Kaliandra terhadap Aktivitas Enzim Diastase, Hidroksimetilfurfural (Hmf) dan Keasaman (Jurnal Ilmu dan Teknologi Hasil Ternak, 2016)
The goal of this study was determine the influence of honey harvesting age in the area of the calliandra plant to diastase enzyme activity, hidroxymetilfurfural (HMF) and acidity. The method of this study was experiments (RAL) with 3 treatments and five replication. The observations of this study were P1 (honey harvested in 11 days), P2 (honey harvested in 14 days), and P3 (honey harvested in 17 days). The variable in this study is the activity of diastase enzyme, hidroxymetilfurfural (HMF) and acidity. Data of this study were analyzed with the Range Analysis (ANOVA), if there is a significant difference between treatments, analysis of data was continued with the Smallest Real Difference Test (BNT). The results of this study showed that the honey harvesting age gave significant effect (p<0.01) on diastase enzymes activities, hidroxymetilfurfural and acidity. As a conclusion, honey harvesting age influences the quality of the activity of the diastase enzyme, hidroxymetilfurfural and acidity. The best content of diastase enzyme, was found in P3 treatment that is generated in 17th day of harvesting with the value 11.12 DN due to it was longer in the nest before harvested. The best content of hidroximetilfurfural was found in P3 with the value 4.48 mg/kg and the best content of acidity honey was found in P3 with the value 28.42 NaOH/kg.